The technique of sutureless total abdominal hysterectomy in gynaecological malignancies: our experience - Nitin Khunteta; Shagun Gupta; Chandrakanta Sulaniya; Vijay Nahata (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: Abdominal hysterectomy is an important part of gynaecological malignancy surgeries. These patients usually have associated comorbidities. Prolonged operating times and post operative complications leave them vulnerable for increased morbidity, mortality and financial burden. By using sealing device for hysterectomy, we have tried to reduce the operating time, blood loss and hospital stays. Objectives: To analyze the outcome of using vessel sealer for doing sutureless hysterectomy in gynaecological malignancies. Methodology: A total of 29 patients satisfying inclusion criteria were included. They underwent appropriate surgery according to the type of malignancy and stage. We calculated duration of surgery, blood loss and hospital stay. Post operative complications and blood transfusions were recorded. We compared our study technique with others conventional suture ligation technique. Results: The mean operating time for TAH with BSO; TAH, BSO with pelvic lymph node dissection (PLND); TAH, BSO, PLND with total omentectomy was 53.33±9.42, 120, 113.125±31.169 min respectively. The mean blood loss was 26.66±4.71, 100, 60±28.5 ml. Mean hospital stay was 4.66±0.94, 6, 7.125±1.9 days respectively. Post operative complications included retention of urine, lymphedema, lymphocele with deep vein thrombosis in one patient each. No mortality was seen. No blood transfusions were required in any patient. Conclusion: Sutureless hysterectomy using vessel sealing device is a good technique to reduce the intraoperative and postoperative morbidity in gynaecological malignancy surgeries. Major advantages being decreased blood loss and duration of surgery.